2018
DOI: 10.1177/1420326x18761114
|View full text |Cite
|
Sign up to set email alerts
|

Association between the emissions of volatile organic compounds from vehicular cabin materials and temperature: Correlation and exposure analysis

Abstract: In-cabin air pollution may be mainly ascribed to the emissions of volatile organic compounds (VOCs) from vehicular cabin materials. Some measurement methods have been proposed by organizations around the world to evaluate the quality of cabin materials. According to the widely used German Standard VDA278, the emission quantity of VOCs from cabin materials over a certain period is taken as an indicator of quality. The VOC emission quantity is generally related to temperature, but the quantitative association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Notably, as individuals often remain indoors longer than outdoors, HCHO pollution indoors must be reduced to avoid potential detrimental effects on human health. Vehicle cabins have been recognized as important indoor environments, and recent reports have shown that the indoor air quality of vehicle cabins is easily polluted by various VOCs (such as toluene) and HCHO 45–47 . Individuals should thus increase the rate of indoor ventilation and cabin, particularly after introducing new sources of HCHO inside, and decrease HCHO pollution indoors or in cabins.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, as individuals often remain indoors longer than outdoors, HCHO pollution indoors must be reduced to avoid potential detrimental effects on human health. Vehicle cabins have been recognized as important indoor environments, and recent reports have shown that the indoor air quality of vehicle cabins is easily polluted by various VOCs (such as toluene) and HCHO 45–47 . Individuals should thus increase the rate of indoor ventilation and cabin, particularly after introducing new sources of HCHO inside, and decrease HCHO pollution indoors or in cabins.…”
Section: Resultsmentioning
confidence: 99%
“…This behavior has already been shown in a number of studies. 6,7 Direct sunlight can heat components such as the instrument panel, resulting in an increase of evaporation of compounds with higher boiling points into the gaseous phase. If a vehicle is subsequently opened, volatile compounds can escape from the passenger cabin, before redeposition on surfaces can occur, an effect which is also known as fogging.…”
Section: Influence Of Temperature and Ventilation On The Odor And Emi...mentioning
confidence: 99%
“…The role of odorants with regard to VIAQ is only sparely discussed in the literature. On the contrary, parameters influencing the emissions and the air quality of the vehicle interior have been comparatively well‐investigated 6,7 . Thereby, the temperature in the vehicle interior, vehicle make, age, and use of deodorizer products have been found to be important determinants of the qualitative and quantitative composition of VOCs that accumulate inside vehicles 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Yang et al derived a theoretical relationship between the VOC emission quantity (M) and temperature (T) with a linear logarithm of MT−1/8 with 1/T, which followed a good linear association (R2: 0.89–0.99). Hence, the VOC emission at different temperatures could be forecasted [15].…”
Section: Possible Pollutantsmentioning
confidence: 99%